Health education in portuguese schools: guidelines from the health and education sectors - Oliveira, Leonel Lusquinhos de Sousa (2019)
Background: In Portugal, all elementary and secondary schools are considered to be Health Promoting Schools. Objective: To analyze the guidelines for the implementation of health promoting schools, issued by the health and education sectors, and assess whether they are consistent with international guidelines. Methodology: Qualitative study, with content analysis of official documents using NVivo®11 Pro software. Results: Both sectors (health and education) care about the Measures to be taken in order to provide organizational and cooperative conditions; define the Objectives clearly, which are coincident; consider active Methodologies/strategies, particularly project methodologies; present similar Areas/themes of intervention; and consider the Assessment essentially quantitative. Conclusion: The health and education documents are convergent and complementary, with articulation between both sectors for an efficient implementation of health promoting schools.